Efektivitas Kepolisian dalam Melakukan Penyelidikan Tindak Pidana Penipuan Online Melalui Media Elektronik Internet - Arini Asriyani; Asti Dwiyanti (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study uses primary data and secondary data. Primary data is obtained directly by the police who handle online fraud cases via the internet, while secondary data is obtained through literature studies. The data were analyzed qualitatively and then presented descriptively by explaining and describing according to the related problems. The results of the study show that: Investigations of online fraud crimes handled by the police are still not effective so the ineffectiveness of the investigation results in a large backlog of cases that are not resolved properly